Elevated plasma syndecan-1 as glycocalyx injury marker predicts unfavorable outcomes after rt-PA intravenous thrombolysis in acute ischemic stroke - Zhao, Fangfang; Wang, Rongliang; Huang, Yuyou; Li, Lingzhi; Zhong, Liyuan; Hu, Yue; Han, Ziping; Fan, Junfen; Liu, Ping; Zheng, Yangmin; Luo, Yumin (Frontiers in Pharmacology, 2022)
Purpose: We aimed to examine the prognostic value of syndecan-1 as a marker of glycocalyx injury in patients with acute ischemic stroke (AIS) receiving rt-PA intravenous thrombolysis. Methods: The study included 108 patients with AIS treated with rt-PA intravenous thrombolysis and 47 healthy controls. Patients were divided into unfavorable and favorable prognosis groups based on modified Rankin Scale scores. Univariate and multivariate logistic regression analyses were used to determine risk factors affecting prognosis. Risk prediction models presented as nomograms. The predictive accuracy and clinical value of the new model were also evaluated. Results: Plasma levels of syndecan-1 were significantly higher in patients with AIS than in controls (p<0.05). Univariate analysis indicated that higher levels of syndecan-1 were more frequent in patients with poor prognosis than in those with good prognosis (t=-4.273, p<0.001). Syndecan-1 alone and in combination with other factors predicted patient outcomes. After adjusting for confounding factors, syndecan-1 levels remained associated with poor prognosis (odds ratio, 1.024; 95% confidence interval [CI], 1.010–1.038). The risk model exhibited a good fit, with an area under the receiver operating characteristic curve of 0.935 (95% CI, 0.888–0.981). The categorical net reclassification index (NRI) and continuous NRI values were >0. The integrated discrimination improvement value was 0.111 (95% CI, 0.049–0.174, p<0.001). Decision curve analysis indicated that the model incorporating syndecan-1 levels was more clinically valuable than the conventional model. Conclusions: Plasma syndecan-1 levels represent a potential marker of prognosis of AIS following intravenous thrombolysis. Adding syndecan-1 to the conventional model may improve risk stratification.